The DESAIN USER INTERFACE PADA APLIKASI E-MONITORING PERKEMBANGAN BELAJAR SANTRI MENGGUNAKAN METODE USER CENTERED DESIGN - Yayak Kartika Sari; Joko Iskandar; Dani Irwansyah (Jurnal Inotera, 2024)
Raudlatul Musthofa Islamic Boarding School is one of the Islamic Boarding Schools located in Tulungagung Regency, Rejotangan District, Raudlatul Musthofa Islamic Boarding School is a boarding school that is a place for students to study general and religious knowledge. There are several problems faced by the boarding school, namely parents / guardians of students do not get regular information about the activities and development of their children at the Raudlatul Musthofa boarding school related to security data, achievements, memorization, and pulan permit information. The management and Ustad / Ustadzah recorded in the book related to security data, discipline, sunnah and compulsory worship, cleanliness and extra activities of each student in the book, so there is no systematic and structured activity report regarding the activities of these students, so that the Management and Ustad / Ustadzah When going to search or use the data must take a long time and have to search one by one because of the large amount of student data in the daily activity book. This research uses the user centered design (UCD) method with stages, namely Specify the context of use, Specify user and organization requirements, Produce design solutions, and Evaluate design against user requirements. The results of the questionnaire calculation using the system usability scale, with 10 questions asked to 10 respondents, it can be concluded that the design of the Website-based Santri Learning Development E-Monitoring application is 88 with the "Acceptable" category and an "Excellent" rating with a grade scale B in other words, this design can be accepted by users.